The Relationship Between Social Media Addiction and Narcissism on Social Media: A Comparison Between Generations Y and Z - Hatice Budak; Mehmet Harmancı (Yeni Medya)
One of the most effective outcomes of social media addiction and narcissistic tendencies is the failure observed in interpersonal relationships. From this perspective, social media addiction and narcissism are not only individual issues but also sociological problems. In this vein, our research aims to examine the levels of social media addiction and narcissistic traits on social media among individuals belonging to Generation Y and Generation Z according to sociodemographic variables, and to identify differences between the two generations. A total of 682 individuals participated in the study, including 328 from Generation Y and 354 from Generation Z, selected through purposive sampling methods, specifically criterion sampling. Participants were administered a sociodemographic information form, the Social Media Addiction Scale-Adult Form, and the Narcissism on Social Media Scale. According to the results of the study, the level of social media addiction and narcissism on social media is significantly higher in Generation Z. There is a moderate positive relationship between social media addiction and narcissism on social media, with narcissism on social media explaining 22,3% of the variance in social media addiction. The findings of the study are discussed in line with the relevant literature, and suggestions for research and practice are offered.